Tinjauan Mobile Government Dalam Pemanfaatan Peluang Digital di Provinsi Jawa Barat - Muhammad Febriansyah Rohimat (JDKP Jurnal Desentralisasi dan Kebijakan Publik, 2021)
Globalization as the estuary of cultural changes and values ​​in society brings drastic transformations. The use of mobile phones and the internet which are increasing every year also requires the government to be able to give innovation to the concept of public services that are integrated with technological changes that are currently happening. The Mobile government which is part of e-government is a concept that should be implemented by the government. The West Java Provincial Government as one of the components of government in Indonesia in taking advantage of these opportunities adapts to technology. Adapting technology as part of government governance is the main focus on implementing mobile government, especially on mobile applications to achieve equitable and integrated public services. The purpose of this study is to analyze the optimization of digital opportunities in West Java Province with the concept of mobile government as the basis for its application. This research is classified as descriptive qualitative. The results show that mobile government has been implemented in the public service process carried out by the West Java Provincial Government. The purpose of this study is to analyze the optimization of digital opportunities in West Java Province with the concept of mobile government as the basis for its application. This research is classified as descriptive qualitative. The results show that mobile government has been implemented in the public service process carried out by the West Java Provincial Government such as Pikobar, Sapawarga, K-MOB, Si Votun Jabar, and Sambara applications.